Social and Behavioral Correlates of Sexually Transmitted Infection– and HIV-Discordant Sexual Partnerships in Bushwick, Brooklyn, New York - Khan, Maria R. (2009)
INTRODUCTION: The Centers for Disease Control and Prevention (CDC) advise repeat HIV testing for partners of HIV-infected persons; injection drug users and their sex partners; individuals with recent multiple partnerships and their sex partners; those involved in sex trade; and men who have sex with men. Additional social and behavioral variables may be useful for identifying priority populations. METHODS: We analyzed data collected during a social network study conducted in a Brooklyn, NY, neighborhood to identify social and behavioral characteristics of respondents (N = 343) involved in HIV-discordant, herpes simplex virus-2– discordant, and chlamydia-discordant partnerships. RESULTS: HIV partnership discordance was associated with injection drug use but was generally not associated with sexual behaviors including multiple partnerships and sex trade. herpes simplex virus-2 and chlamydia partnership discordance were associated with multiple partnerships, sex trade, and same sex partnership history. Additional correlates of sexually transmitted infection (STI)/HIV–discordant partnerships included older age (≥25 years), noninjection drug use, and incarceration history. Analyses suggested that screening tools composed of CDC-recommended sexual risk and injection drug indicators plus indicators of older age, noninjection drug use, and incarceration were more effective in identifying STI/HIV priority populations than tools composed of CDC indicators alone. CONCLUSIONS: Screening tools that include social and behavioral indicators may improve STI/HIV case-finding effectiveness.